1997
DOI: 10.1002/hep.510250336
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T Lymphocyte Response and Viral Load in Hepatitis C Virus Infection

Abstract: 1liver-infiltrating lymphocytes 4 of patients with chronic hepa-A cytotoxic T lymphocyte (CTL) response to the hepatitis C, the role of CTL responses in HCV infection is untitis C virus (HCV) nucleoprotein residues 88-96 that are known. HCV infection frequently persists and is implicated the minimal and optimal epitope for human leukocyte in the development of chronic hepatitis, cirrhosis, and hepatoantigen (HLA) B44-restricted CTLs was assessed in 27 cellular carcinoma. 5 Posttransfusion HCV infection has de-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
99
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 36 publications
2
99
1
Order By: Relevance
“…We and others have reported that patients with higher levels of HCV-specific CTL activity have lower levels of viremia. 7,24,25 Viral levels tended to be lower within those patients that had intrahepatic HCV-specific CTL in this study, but this did not reach statistical significance. This is likely because of the relatively small patient numbers in this report.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We and others have reported that patients with higher levels of HCV-specific CTL activity have lower levels of viremia. 7,24,25 Viral levels tended to be lower within those patients that had intrahepatic HCV-specific CTL in this study, but this did not reach statistical significance. This is likely because of the relatively small patient numbers in this report.…”
Section: Discussionmentioning
confidence: 56%
“…Imawari et al recently reported that a high HCV-specific CTL response to the nucleoprotein (aa 88-96) was associated with a low titer of serum HCV RNA in HLA B44-positive patients infected with HCV. 24 Thus, CTL response to the core protein may also improve response through lower pretreatment viral levels. A similar role for CD4 ϩ core epitopes has been described for the CD4 ϩ response to HCV.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] In contrast, chronic infection is characterized by low frequencies of CD8 ϩ T cells in peripheral blood. [16][17][18][19][20][21] Although the cellular immune response may be less vigorous and more narrowly directed in those who fail to clear the infection, a cellular immune response is nonetheless often present in early infection and may even persist into chronic infection. Why those immune responses fail to control infection is unclear, but responses generated in acute infection have been shown to decline in a few subjects who remained persistently infected.…”
mentioning
confidence: 99%
“…Most immunological studies in this setting have thus focused on peripheral blood cells, which may not accurately reflect the composition and function of the hepatic infiltrate. The low frequency of HCV-specific CD8 T cells in the circulation of chronically infected patients [4][5][6][7][8] has been attributed to their sequestration in the liver. This is based on work on intrahepatic lymphocytes isolated from liver biopsy material and studied either after in vitro amplification [9][10][11] or directly ex vivo.…”
mentioning
confidence: 99%